Transcriptome Analysis Showed a Differential Signature between Invasive and Non-invasive Corticotrophinomas - de Araújo, Leonardo Jose Tadeu; Lerario, Antonio Marcondes; de Castro, Margaret; Martins, Clarissa Silva; Bronstein, Marcello Delano; Machado, Marcio Carlos; Trarbach, Ericka Barbosa; Villares Fragoso, Maria Candida Barisson (Frontiers in Endocrinology, 2017)
ACTH-dependent hypercortisolism caused by a pituitary adenoma (Cushing’s disease, CD) is the most common cause of endogenous Cushing’s syndrome. CD is often associated with several morbidities, including hypertension, diabetes, osteoporosis/bone fractures, secondary infections, and increased cardiovascular mortality. While the majority (≈80%) of the corticotrophinomas visible on pituitary MRI are microadenomas (<10 mm of diameter, MIC), some tumors are macroadenomas (>10 mm, MAC) with increased growth potential and invasiveness, exceptionally exhibiting malignant demeanor. In addition, larger and invasive MAC are associated with a significant increased risk of local complications, such as hypopituitarism and visual defects. Given the clinical and molecular heterogeneity of corticotrophinomas, the aim of this study was to investigate the pattern of genetic differential expression between MIC and MAC, including the invasiveness grade as a criterion for categorizing these tumors. In this study, were included tumor samples from patients with clinical, laboratorial, radiological and histopathological diagnosis of hypercortisolism due to an ACTH-producing pituitary adenoma. Differential gene expression was studied using an Affymetrix microarray platform in 12 corticotrophinomas, classified as non-invasive MIC (n=4) and MAC (n=5), and invasive MAC (n=3), according to modified Hardy criteria. Somatic mutations in USP8 were also investigated, but none of the patients exhibited USP8 variants. Differential expression analysis demonstrated that non-invasive MIC and MAC have a similar genetic signature, while invasive macroadenomas exhibited a differential expression profile. Among the genes differentially expressed, we highlighted CCND2, ZNF676, DAPK1 and TIMP2 and their differential expression was validated through qRT-PCR in another cohort of 15 non-invasive and 3 invasive cortocotrophinomas. We also identified potential biological pathways associated with growth and invasiveness, TGF-β and G protein signaling pathways, DNA damage response pathway and pathways associated with focal adhesion. Our study revealed a differential pattern of genetic signature in a sub-group of MAC, supporting a genetic influence on corticotrophinomas in patients with CD.